A Compact Square and Hexagonal Antennas with Fractal DGS for Mobile Satellite Applications (Journal of Pharmaceutical Negative Results, 2022)
A miniaturized Circularly Polarized Microstrip Patch Antenna with fractal Defected Ground Structure (DGS) is proposed. For the purpose of realizing Circularly Polarized radiation, two square notches and an asymmetric length of two rectangular slots that are perpendicular to one another are printed on square and hexagonal shaped patches, respectively. The antenna size is decreased and circular polarization is achieved by employing koch snowflake-shaped Defected Ground Structure. The proposed antenna is appropriate for use in India with mobile satellite communications. The suggested antennas resonate at 1.5GHz. Axial Ratio, VSWR, Radiation Efficiency, FBR (Front to Back Ratio), and Area of Patch are the metrics used to evaluate the antenna performance to that of the existing antenna. It is observed that the proposed structures are better in many aspects mentioned above. The antennas are simulated using HFSS v.2017.2 software.